Uji Aktivitas Ekstrak Etanol Daun Labu Siam (Sechium edule Jacq. Swartz) sebagai Antibakteri Mycobakterium smegmatis - Christel Sambou; Douglas N. Pareta; Sarah Sambow; Wilmar Maarisit; Jabes Kanter; Jeane Mongi; Hanna M. Rumagit; Selvana Tulandi; Joke L. Tombuku; Reky R. Palandi; Nerni O. Potalangi (Journal of Pharmaceutical and Sciences, 2023)
The membrane structure of Mycobacterium smegmatis is similar to that of Mycobacterium tuberculosis, allowing TB testing to be performed on Mycobacterium smegmatis without directly testing on Mycobacterium tuberculosis. Antibacterial testing uses the paper disc method with several treatments, namely extract concentrations of 1 µg/disc, 2 µg/disc, and 4 µg/disc, as well as positive control streptomycin 2 µg/disc and negative control 70% ethanol. The research results obtained at Extract Concentrations of 1, 2, and 4 µg/disc have moderate antibacterial activity seen from the inhibitory zone diameter, namely 8.73 mm, 9.17 mm, and 9.73 mm, and the positive control is strong because it has a zone diameter of 13.27 and the negative control does not give a zone. The conclusion is that the extract of siam pumpkin leaves has moderate antibacterial activity.